Sertifikat Wakaf Upaya Menjaga Eksistensi Harta Wakaf - Mohamad Ma'mun (LPPM IAI Hasanuddin Pare-Kediri, 2021)
Waqf is one of the concepts of giving in Islam which has a strategic position. Waqf has a vertical dimension, namely a relationship with the Creator, and a horizontal relationship (among humans). If waqf is managed properly, the benefits will be felt by fellow humans. One of the most urgent aspects of waqf is the waqf certificate. If the property has been certified, then the waqf object will be legally enforceable and cannot be transferred. In the present, land prices are soaring, economic needs are also getting bigger, the temptation to control waqf property is very big. With a certificate of waqf, the management of waqf assets can be maximized. The legal basis for the waqf certificate is found in the Al-Quran, Al-Hadith and also the ijtihad of the scholars'. The procedure for the waqf certificate has been explained in the decision of the Director General of Islamic Community Guidance